ESTER ASAM KARBOKSILAT DAN ISOPROPIL ALKOHOL UNTUK BAHAN DASAR BIOPELUMAS - Mahreni Mahreni; Faizah Hadi; Renung Reningtyas; Gemal Kurniawan; Maulana Fahdlurahman Al Abdillah (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2017)
ESTERIFICATION OF OLEIC ACID, STEARIC ACID AND ISOPROPIL ALCOHOL FOR LUBRICANT BASE.Uncontrolled spill of petroleum base lubricant has been polluted the environment. An alternative of biodegradable and environmental friendly lubricant is needed to substitute petroleum based lubricant. Biolubricant can be made from plant or animal oil, or synthetic lubricant that meets biodegradability criteria and nontoxic to human and environment. The aim of this research is to produce ester from Oleic acid, Stearic acid and Isopropyl alcohol as a base stock for lubricant. Range of time in reaction was set 3,4, and 5 hour. Stearic acid was varied 11-15 gram, Oleic acid 85- 89 ml, and IPA 10-15 ml. The resulting products of ester were confirmed by FTIR. Kinematic viscosity, Pour point, Freezing pont are evaluated by ASTM analyses. Ester produced from 12 gr oleic acid, 88 ml of oleic acid and 5 mil of IPA at room temperature is still in liquid phase, with kinematic viscosity at 100oCis larger than 4,099 mm2/s, Pour point 24oC and Freezing point = 12oC.This ester is potential to be used as biolubricant base stock.